Strategi Guru dalam Meningkatkan Minat Baca di SMA PGRI Malangbong Tanpa Perpustakaan - Nanda Yudisman, Septevan; Jalinur; Prambudi, Danang (Perpustakaan Universitas Gadjah Mada, 2025)
This study explains how teachers can help enhance students' reading interest at SMA PGRI Malangbong, a newly established school without a library. The research questions aim to uncover teachers' strategies in acting as literacy promoters despite existing limitations. This qualitative study employs a case study design through observation, in-depth interviews, questionnaires, and document analysis. Literacy challenges and strategies were identified through data analysis using the Miles and Huberman model. The findings indicate that the absence of a library hinders students' access to reading materials. To serve as effective coordinators for this purpose, teachers adopt innovative methods to manage books, including bringing books from home, shared reading time, literacy games, book review assignments, and more. Although limited facilities are perceived as obstacles, these strategies successfully boost students' motivation. Additionally, factors such as the low reading culture within families and unsupportive digital media also influence students' reading interest. In summary, teachers act as both library substitutes and literacy promoters. However, this role cannot be fulfilled in isolation it requires investment in training, reading materials, and partnerships with communities and government. Therefore, this study provides strategic recommendations for developing sustainable literacy policies for schools with limited facilities.